2019
DOI: 10.4103/bc.bc_11_19
|View full text |Cite
|
Sign up to set email alerts
|

Developments in hybrid operating room, neurointensive care unit, and ward composition and organization for stroke management

Abstract: Stroke is the leading cause of adult disability in the US. Rapid diagnosis and treatment of stroke, in addition to efficacious rehabilitation, is invaluable. The present review aims to report the recent improvements in hybrid operating rooms (hybrid ORs), and in the organization of Neurological intensive care unit (NICUs) and dedicated stroke wards (SWs), which contribute to enhanced stroke treatment. A PubMed literature review was conducted in addition to the collection of other online media releases regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…42,43 Despite this, evidence from the scientific literature suggests potential for broader applications, as seen in countries like the Netherlands, 49 Denmark, 50 and the United States. 51 Nonetheless, the level of detail in existing publications about hospital structures is basic with a predominant focus on clinical variables. A key benefit of our results is the potential to conduct validation studies using existing databases.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 Despite this, evidence from the scientific literature suggests potential for broader applications, as seen in countries like the Netherlands, 49 Denmark, 50 and the United States. 51 Nonetheless, the level of detail in existing publications about hospital structures is basic with a predominant focus on clinical variables. A key benefit of our results is the potential to conduct validation studies using existing databases.…”
Section: Discussionmentioning
confidence: 99%
“…As the first contact medical personnel and the whole-process manager of stroke patients, nurses perform a vital role in evaluation, diagnosis, and treatment [ 21 , 22 ]. Recent studies have demonstrated the effectiveness of nurses in the treatment of stroke patients [ 22 ].…”
Section: Discussionmentioning
confidence: 99%